Evaluation of the museum activities related to the school curricula for the two seminars the first and second in the UAE: the case of the Sharjah museums - Alnaqbi, Mariam; Jamhawi, Monther; Sukkar, Ahmad (Al-Adab Journal, 2024)
The study aimed to evaluate the museums of the Emirate of Sharjah through museum activities and their role in the educational and culture process, to discover the types of museum activities and educational programs offered to students and related to the school curricula, to encourage future generations and educational institutions of the importance of the role of museums and their visits to places that preserve the country's heritage and make them feel the spirit of belonging to this homeland.The study population consisted of museums in the Emirate of Sharjah. The questionnaire was distributed via the Internet. 70 individuals from various disciplines responded. The researcher used the arithmetic means and standard deviations, in addition to the Cronbach alpha test, the Pearson test and the Eta square test to determine the size of the effect represented by the four axes: the museum's educational function and educational, museum holdings, museum activities, museum management and staff.The study reached a number of conclusions, including:There are no statistically significant differences at the significance level 0.05 about the importance of museum activities and their availability in Sharjah museums, and there are no statistically significant differences at the significance level 0.05. About the sample’s agreement on the educational and educational function of the museum. “There are no statistically significant differences at the level of significance 0.05 about the availability of museum holdings that contribute to supporting the function of the museum.” There were no statistically significant differences at the level of significance 0.05 about the contribution of museum management and workers in supporting the function of the museum. One of the results is that the effect size of all four axes on the independent variables was medium with regard to nationality and academic achievement, while the size was large in the rest of the independent variables of the four axes of the questionnaire, museum departments in Sharjah have prior knowledge of the Emirati curricula, through which workshops related to school curricula topics are prepared, which enhance the value of the Emirati heritage.In light of the results of the study, the study recommended the need to cooperate with museum departments in activating museum activities and the need to focus on the cultural and educational construction of generations and linking them to their past and heritage. It also recommended those in charge of the educational process in the first and second cycle of the need to re-plan classes for activities, national education, and social studies in its branches, so that museums’ holdings, activities, and programs are used to develop national and social education skills for students in schools.